PENERAPAN TANADASHIP PADA KECEMASAN PASIEN KOMORBID DENGAN COVID-19 - Slametiningsih, Slametiningsih; Kurwiyah, Neneng; Nuraenah, Nuraenah; Khalila, Rhadiatan; Larasati, Putri (Jurnal Ilmiah Keperawatan, 2022)
Covid-19 or corona virus disease is a new strain of coronaviruses. This disease firstly reported in the city of Wuhan, China, In December 2019. The spread of the virus swiftly became a global health threat. It is believed that patient with chronic diseases such as diabetes, cardiovascular diseases, auto-immune disease, kidney failure, hypertension, chronic obstructive pulmonary disease, and cancer, are susceptible to respiratory failure and may have poorer outcome. Covid-19 patient who present with a comorbid condition may experiencing physically and psychological changes. In addition, negative information and stigma in society can cause psychosocial problems, such as anxiety. Aim: This study aims to overcome anxiety by using TANADASHIP. TANADASHIP is a collection of actions include deep breathing, spiritual and five finger hypnosis. Method: In experimental study, using pre-post design, a total of 28 Covid-19 patients with comorbid were included. Before and after intervention, anxiety scale was used to measure and record patient anxiety. Data analysis was performed using SPSS 25.0 Software. Results: The average anxiety score before intervention was not statistically significant (p = 0.052). Discussion:based on the calculation of the data, it was found that there was a decrease in the level of anxiety in the respondents, which previously obtained 14 respondents experiencing anxiety after the intervention using video, it was found that only 6 respondents still experienced anxiety with a mild level of anxiety. Conclusion:Based on the results of the study, the use of the TANADASHIP method is very suitable for reducing anxiety levels. Researchers assess very effective in any situation and condition